STRATEGI PENGEMBANGAN DESA WISATA PENTINGSARI DESA UMBULHARJO KECAMATAN CANGKRINGAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Yosi Darojot; Teguh Kismantoroadji; Daru Retnowati (Jurnal Dinamika Sosial Ekonomi, 2017)
This study aims to (1) Analyze the strategies applied in the development of Pentingsari Tourism Village, Umbulharjo Village Cangkringan Subdistrict, Sleman District of Yogyakarta Special Region based on SWOT Matrix (Strength, Weakness, Opportunity, Threat), (2) Analyze strategic decision-making based on QSPM matrix (Quantitative Strategic Planning Matrix). This research is a quantitative research with implementation methods using case studies, taking saturated sampling of respondents (sampling census)with the retrieval of 30 managers. Data collection techniques used were interviews, observations, questionnaires, literature studies and documentation while for data analysis techniques will be tested with IFE (Internal Factor Evaluation) matrix and EFE matrix (External Factor Evaluation), IE (Internal External) matrix, SWOT matrix (Strength, Weakness, Opportunity, Threat) and QSPM (Quantitative Strategic Planning Matrix) matrix. The result of this study concludes that (1) The strategy applied in Pentingsari Village, Umbulharjo Village, Cangkringan Subdistrict, Sleman District, Yogyakarta Special Region based on SWOT matrix is SO strategy (Strengths Opportunty), (2) The appropriate strategy decision is applied in Development of Pentingsari Tourism Village, Umbulharjo Village, Cangkringan District, Sleman Regency, Yogyakarta Special Region is a market penetration strategy. Keywords: Pentingsari Tourism Village, Development Strategy